Fear of missing out (FoMO) dengan social comparison pada mahasiswa pengguna Instagram - Cahyani, Reina Okta; Pangestuti, Retno (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2023)
Abstract: The purpose of this study was to determine the relationship between fear of missing out (FoMO) and social comparison among college students who use Instagram with a correlational quantitative research type. The research was conducted on a sample of 360 students using cluster random sampling technique. The data collection technique uses a questionnaire with a Likert scale model which is distributed with the help of the Google Form application. Instrument test using validity test and reliability test. Measuring tools used are Pzybylsky’s Fear of Missing Out (FoMO) scale and social comparison scale which refers to Festinger’s theory. To test data analysis using the normality test with the Kolmogorov-Smirnov technique, linearity test, and hypothesis testing with the help of the SPSS application version 26 for Windows. The results of the study used Spearman's rho nonparametric test analysis which showed that Ha was accepted and H0 was rejected. So it can be concluded that there is a positive relationship between fear of missing out with a correlation coefficient of 0.654; p=0.000 (p0.05). That is, the higher the level of fear of missing out, the higher the level of social comparison among students and vice versa.Keywords: fear of missing out, social comparison, instagram